PERAN IMUM MUKIM MENANGANI KASUS KEKERASAN RUMAH TANGGA: SEBUAH UPAYA MEYELESAIKAN PERKARA MELALUI PERDAMAIAN - Rahmat Ananda Prakasa Rahmat; Analiansyah; Khairani Mukdin (Prodi Magister Hukum Keluarga Pascasarjana UIN Ar-Raniry Banda Aceh, 2024)
Domestic violence (DV), according to Law No. 23 of 2004, refers to any act against a person, particularly women, resulting in physical, sexual, psychological, and/or household neglect causing suffering or distress. Efforts to resolve DV cases at the village level are not always successful, with some cases needing referral to the Mukim level. The settlement by the Imum Mukim for DV cases in Mukim Tungkop can be achieved through a mediation approach. Despite the mediation used by the Imum Mukim, the exact process remains unclear. Therefore, the author attempts to address this issue to find answers: first, what methods does the Imum Mukim use to resolve domestic violence (DV) cases in Mukim Tungkop? Second, what is the Islamic law perspective on the resolution of DV cases by the Imum Mukim in Mukim Tungkop?. The research type in this thesis is descriptive qualitative, where data obtained will be systematically organized, analyzed into units, synthesized, structured into patterns, and conclusions drawn based on significance and lessons learned. The conclusions of this research are twofold: firstly, the approach taken by the Imum Mukim Tungkop in resolving DV cases involves mediating disputes and arbitrating decisions, and secondly, the process aligns with Islamic teachings as per the Qanun Aceh, which is designed based on Islamic Sharia. The Imum Mukim approach also adheres to Islamic principles and concepts of seeking reconciliation (ishlah) through mediation (tahkim).